Charlie and the Chocolate Factory - "Dahl, Roald" (Penguin Books Ltd., 2014 UK, 2014)
Mr Willy Wonka, the most wondrous inventor in the world, opens his gates of his amazing chocolate factory to five lucky children. Gobstoppers, wriggle sweets and a river of melted chocolate delight await - Charlie needs just one Golden Ticket and these delicious treats could all be his!